Standardized catch rates in biomass for the north Atlantic stock of swordfish (Xiphias gladius) from the Spanish surface longline fleet for the period 1986-2011 - García-Cortés, Blanca; Ramos-Cartelle, Ana; Mejuto-García, Jaime (2014)
Nominal catch rates of the Spanish surface longline fleet targeting swordfish are provided for a period of 26 years (1986-2011). Standardized catch rates (in number of fish and weight) were also updated using log-normal Generalized Lineal Models (GLM). Factors such as area, quarter, gear, bait as well as the fishing strategy -based on the ratio between both most prevalent and appreciated species by skippers- were used. The models explained the 54% and 55% of the CPUE variability in number and weight, respectively. The results show an overall slightly decreased trend of the standardized CPUE in number and weight up to years 1996 and 1998, respectively, followed by a change of trend afterwards. The standardized mean weights are also provided for the same period.